Generic mouse heart scaffold - Christie, Richard; Osanlouy, Mahyar; Hunter, Peter (SPARC Portal, 2022)
Annotated heart scaffold for mouse available for registration of segmented neural anatomical-functional mapping of cardiac neural circuits.